Public Knowledge about and Detection of Canine Visceral Leishmaniasis in Urban Divinópolis, Brazil - Carina Margonari; Júlia Alves Menezes; Marcele Neves Rocha; Kamila Nunes Maia; Michael Éder de Oliveira; Amanda Luisa Fonseca; Fabrizio Furtado de Sousa; Eduardo de Castro Ferreira; Ana Paula Madureira; Maria Norma Melo; Rodrigo Pedro Soares (Journal of Tropical Medicine)
Background. Leishmaniases are diseases with a wide spectrum of clinical manifestations including cutaneous (CL) and visceral (VL) forms. Many factors may affect their occurrence and expansion including environmental, geographic, and social conditions. In the past two decades, Divinópolis, Minas Gerais State, Brazil, has exhibited the potential for a disease outbreak, with the appearance of CL, and VL cases (human and canine). Hence, this study was initiated to monitor public knowledge of the disease. Questionnaires were administered in four neighborhoods (Jardim Belvedere, Esplanada, Danilo Passos I and II) where most of the human and canine cases have been reported. The analyses demonstrated that public knowledge of the disease is sparse and fragmented. A strong perception of the dog as the main reservoir was observed. Five veterinary clinics were evaluated for the presence of canine VL using serological (RIFI and ELISA) and molecular (PCR-RFLP) techniques. This is the first study demonstrating the occurrence of Leishmania infantum in Divinópolis, suggesting a possible urbanization of VL.